2014
DOI: 10.1021/jo500050n
|View full text |Cite
|
Sign up to set email alerts
|

Diastereoselective Synthesis of γ- and δ-Lactams from Imines and Sulfone-Substituted Anhydrides

Abstract: Sulfone-substituted γ- and δ-lactams have been prepared in a single step with high diastereoselectivity. Sulfonylglutaric anhydrides produce intermediates that readily decarboxylate to provide δ-lactams with high diastereoselectivity. Substituents at the 3- or 4-position of the glutaric anhydride induce high levels of stereocontrol. Sulfonylsuccinic anhydrides produce intermediate carboxylic acids that can be trapped as methyl esters or allowed to decarboxylate under mild conditions. This method has been appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 31 publications
0
38
0
Order By: Relevance
“…Recent studies in our group have revealed that isolation and purification of the imines results in increased yields in the subsequent AMR reaction; [5] therefore, we appliedt his approach to our current system and noticed as imilar increase in yield. The reactiont olerates av ariety of electron-donatinga nd electron-withdrawing substituents aroundt he aldehyde or aniline component;h owever,v ery electron-rich systems (entries1and 11)p rovide significant reductions in the reactiony ield.…”
Section: Scheme1a)mentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies in our group have revealed that isolation and purification of the imines results in increased yields in the subsequent AMR reaction; [5] therefore, we appliedt his approach to our current system and noticed as imilar increase in yield. The reactiont olerates av ariety of electron-donatinga nd electron-withdrawing substituents aroundt he aldehyde or aniline component;h owever,v ery electron-rich systems (entries1and 11)p rovide significant reductions in the reactiony ield.…”
Section: Scheme1a)mentioning
confidence: 91%
“…[5] This was the first report using an activated glutaric anhydride in aC astagnolitype reaction. The successo ft hose studiesp aired with our previousw ork on synthesis of g-lactams (2-pyrrolidinones) from cyanosuccinic anhydrides prompted us to explore the reactions of glutarica nhydrides, which would form d-lactams (2-piperidinones).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, we are not aware of any reports on the use of aldimines derived from strongly deactivating p -nitrobenzaldehyde in the anhydride-Mannich reaction. 14 It is therefore a testament to the enhanced reactivity of 2 that it undergoes satisfactory annulation with 1c. Understandably, ortho -substituted styrenes react with a slight decrease in efficiency (3c2 vs. 3c4 or 3c3 vs. 3c5).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the development of a new synthetic method for δ‐lactams is highly desired. There are several synthetic methods for δ‐lactams, including aza‐annulation of β‐enamino carbonyl substrates with acrylate derivative, [5h] reductive deamination of α‐aminocarbonyl compounds, [5e,g,6] palladium‐catalyzed intramolecular δ‐lactam formation of aryl halides and amide‐enolates, [5f] palladium‐catalyzed C−H activation reactions, [7] regiospecific 6‐endo‐annulation of in situ generated 3,4‐dienamides, [8] and anhydride Mannich reactions using sulfone‐substituted anhydrides [9] . In 2018, Rovis et al.…”
Section: Methodsmentioning
confidence: 99%
“…There are several synthetic methods for δ-lactams, including aza-annulation of β-enamino carbonyl substrates with acrylate derivative, [5h] reductive deamination of α-aminocarbonyl compounds, [5e,g,6] palladium-catalyzed intramolecular δ-lactam formation of aryl halides and amide-enolates, [5f] palladiumcatalyzed CÀ H activation reactions, [7] regiospecific 6-endoannulation of in situ generated 3,4-dienamides, [8] and anhydride Mannich reactions using sulfone-substituted anhydrides. [9] In 2018, Rovis et al reported the synthesis of these compounds via regiodivergent iridium(III)-catalyzed diamination of alkenyl amides with secondary amines. [10] In 2020, Rovis et al also reported the synthesis of δ-lactams by Rh-catalyzed CÀ H activation/annulation method using N-pivaloyloxy acrylamides with unactivated alkenes.…”
mentioning
confidence: 99%